Factors Affecting The Implementation of Performance-Based Budgeting Policies: Communication, Resources, and Bureaucratic Structure - Cris Kuntadi; Nurma Livrianti (Journal Research of Social Science, Economics, and Management, 2022)
This study reviews the factors that influence the implementation of performance-based budgeting policies as the dependent variable on communication, resources, and bureaucratic structure as independent variables in a literature study of state financial management. This research is a literature review that aims to build a hypothesis of the influence between variables so that it can be used in further research. This study shows that communication, resources, and bureaucratic structure affect the implementation of performance-based budgeting policies. The research method for this scientific article is a literature review and qualitative method through the identification of several relevant works of literature which are classified based on the relevance and quality of the literature found and examines theories and relationships or influences between variables from books and journals both offline and offline. in libraries and online sources from Mendeley, Google Scholar, and other online media. The results of this study can be concluded that: Communication affects the implementation of performance-based budgeting policies. Resources affect the implementation of performance-based budgeting policies. The bureaucratic structure affects the implementation of performance-based budgeting policies.